Technology-Based Accessibility in Recruitment and Workforce Placement by the Berdaya Menembus Batas Foundation to Increase Employment Opportunities for Persons with Disabilities - Abdul Majid; Imam Nazarudin Latif; Ivana Nina Esterlin Barus (Postgraduate, University of Mataram, 2026)
This study aims to examine the effect of technology-based recruitment accessibility and technology-supported job placement mechanisms on increasing employment opportunities for people with disabilities within the inclusive employment program implemented by the Berdaya Menembus Batas Foundation. The research is motivated by the persistently low labor force participation rate of persons with disabilities, which indicates the presence of structural and technological barriers in accessing decent employment. This study employs a quantitative approach with a descriptive–verificative research design. Data was collected through a five-point Likert scale questionnaire distributed to people with disabilities who had experienced digital recruitment and technology-assisted job placement processes. The collected data were analyzed using multiple linear regression analysis. The findings indicate that respondents generally perceive recruitment accessibility, workforce placement mechanisms, and employment opportunities positively, with mean scores above 4.00 and relatively low standard deviations, suggesting consistent perceptions among participants. The reliability test also confirms that the research instrument is highly reliable, with Cronbach’s Alpha values above 0.80 for all variables. Furthermore, regression analysis shows that technology-based recruitment accessibility and workforce placement mechanisms simultaneously have a positive and significant effect on employment opportunities (F = 45.128; Sig. = 0.000), with a coefficient of determination (R²) of 0.612, indicating that 61.2% of the variation in employment opportunities can be explained by the two variables. Partially, both variables also demonstrate positive and significant effects, where recruitment accessibility emerges as the dominant factor (β = 0.487), followed by workforce placement mechanisms (β = 0.362). These findings suggest that accessible digital recruitment systems combined with effective technology-supported placement mechanisms form an integrated, inclusive employment ecosystem capable of reducing structural barriers and improving labor market participation for people with disabilities. Therefore, the integration of technology-based recruitment systems and competency-based workforce placement strategies is essential for expanding employment opportunities and fostering a more inclusive, equitable, and sustainable labor market.